Perception of bullying in sixth year students of a Lima public university school of medicine 2015 - Oliveros Donohue, Miguel (2016)
Introduction. Aggressive and discriminatory behavior affects physical and mental health even on those who commit them. Students are subjected to stress, which increases the risk of those behaviors and makes them likely to suffer from its consequences. On the other hand, the Medical School aims to educate medical professionals integrally, with abilities to avoid violence and live peacefully. That is why the interest of describing this problem in Universidad Nacional Mayor de San Marcos, Lima, Peru’s Medical School. Objective. To address violence in students from the sixth year of Human Medicine who had not participated in the Integral Formation Program in UNMSM. Design: Descriptive, transversal study. Setting. "Instituto Nacional del Niño", Lima, Peru, teaching hospital. Participants. Sample consisted in 93 (63%) students enrolled in the sixth year of the Faculty of Medicine who took the course of Pediatrics during the months of July to November 2015. Interventions. An instrument developed and validated by the Spanish Office of the Ombudsman, modified and corrected by Hoyos et al was used. Frequencies and percentages of responses were calculated. Results. Violent behaviors were more prevalent among students; the most practiced behavior was to express badly (40.8%). Conclusions. The existence of violence occurs in a high percentage of the studied population; teachers and students are involved.